Removal of nitrogenuos and phosphorus compound from shrimp waste using seaweed, Gracilariaedulis - Azizah, Endut; Khatoona, Helena; Siti Rashidah, Togimin; Banarjee, Sanjoy (2013)
The fast growing shrimp farming industry had cause degrading near shore water quality through nutrient enrichment. Shrimp effluent is absolutely high in nitrogen and phosphorus compound result from animal feaces, added fertilizer and uneaten food. These phenomena could create an eutrophication problem in coastal waters. The aim of this study is to evaluate the potential of locally available Gracilaria species (Gracilaria edulis) for reducing the nitrogenous and phosphorus compound from shrimp pond waste in a recirculating water system model. A set of tank with capacity 144L was set up to create a system by applying the gravity to flow the effluent. The treatment tank was added with 5kg/tank of seaweed while the control was left empty. Results showed that the Gracilaria edulis significantly (P<0.05) reduces the unionized ammonia and nitrite compound compared to the control (P<0.05). It was also found that the phosphorus and nitrate levels showed a fluctuation along the experimental period, but this value still maintain at the safe.